2012
DOI: 10.1159/000342634
|View full text |Cite
|
Sign up to set email alerts
|

Early Systolic Blood Pressure Changes in Incident Hemodialysis Patients Are Associated with Mortality in the First Year

Abstract: Background: In incident hemodialysis (HD) patients, the relationship between early systolic blood pressure (SBP) dynamics and mortality is unknown. Methods: Baseline SBP levels were stratified into 5 categories ranging from <120 and ≥180 mm Hg. Early pre-HD SBP change was defined as the slope of pre-HD SBP from week 1 to 12 and categorized in quartiles (Q1, lowest slope). SBP slopes were computed for each patient by simple linear regression. Results: In 3,446 incident HD patients (42% females, 44% black, age 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 38 publications
0
12
1
Order By: Relevance
“…In the aforementioned study of Renal Research Institute facilities, mean SBP declined sharply between the first and second weeks of treatment, from 150.5 to 147.7 mm Hg, before increasing during the rest of the first 12 weeks of treatment. 6 However, the aggregate pattern belies heterogeneity in SBP trends by initial SBP. In patients with severe hypertension (ie, initial SBP .…”
Section: Prevalence After Dialysis Initiationmentioning
confidence: 96%
“…In the aforementioned study of Renal Research Institute facilities, mean SBP declined sharply between the first and second weeks of treatment, from 150.5 to 147.7 mm Hg, before increasing during the rest of the first 12 weeks of treatment. 6 However, the aggregate pattern belies heterogeneity in SBP trends by initial SBP. In patients with severe hypertension (ie, initial SBP .…”
Section: Prevalence After Dialysis Initiationmentioning
confidence: 96%
“…In contrast, a study comprising 3446 incident dialysis patients of a US provider [ 32 ] showed an initial decrease in systolic BP within the first week after the start of dialysis, followed by a steady increase and a plateau phase after 12 weeks. No major differences in mean pre-dialytic systolic BP levels in the overall cohort were observed between the start of dialysis and a 1-year follow-up period [ 32 ]. Also in this study, low pre-dialytic BP (defined as systolic BP <120 mmHg) at the start of dialysis was associated with increased early (6–12 weeks) mortality.…”
Section: Cardiovascular Parametersmentioning
confidence: 99%
“…It has been shown that trajectories of common clinical and laboratory parameters following the start of dialysis were related to increased mortality. This was true even for downward trends in serum albumin and body weight, and both upward and downward trends of predialytic systolic BP and body temperature [56][57][58][59][60] (Fig. 3).…”
Section: Predicting the Future: Forward Trajectoriesmentioning
confidence: 84%